Economic Growth and Firm Size Dynamics: Evidence from Romania’s Development Regions - Daniel Badulescu; Alina Badulescu; Ramona Simut; Dragos Dianu (Theory, Methodology, Practice, 2024)
The relationship between firms and economic growth is an intensely debated topic in the literature, emphasizing the impact of the large businesses or small and medium-sized enterprises (SMEs) in ensuring growth, innovation and employment, the role of support measures or social benefits. Although the importance of each category in growth and development is far from a consensus, there is a tacit recognition that each size-class of firms has a series of specific characteristics that can better influence certain aspects of development. A better knowing of them could help adapting and calibrating measures and policies according to specific objectives, stages or geographical areas. In this paper, we propose an econometric approach to the relationship between economic growth (by GDP evolution) and the dynamics of the firms’ sector, by size class, at the level of the development regions of Romania. We found that the effect of the number of enterprises in each size class similarly influences the GDP, regardless of the region, with a more pronounced positively impact in the case of micro- and small enterprises and ambiguous in the case of medium-sized enterprises.